Conceptualization of Women's Physical Beauty in Javanese Metaphors - Kurnia, Ermi Dyah (Sutasoma : Jurnal Sastra Jawa, 2021)
Like other societies, women are important figures in Javanese society so that women's figures in Javanese society's thoughts are also described in such a way. There is a desire in the collective imagination of the Javanese community towards women, so that the Javanese people's thoughts about women are very diverse. One of them is the Javanese thought about the physical beauty of women which is idealized through the use of metaphors. This metaphor in Javanese society is an expression of Javanese society to express ideas and dreams through language. This paper aims to find out the metaphorical conceptualization of the physical beauty of women in Javanese. This study uses qualitative methods and conceptual metaphor theory according to Lakoff and Johnson (1980). The results of data analysis show that there is a relationship between the Javanese people and their natural environment in the form of physical and cultural. Physical environment in the form of animals, plants, and other objects around it